Attendance Check System and Implementation for Wi-Fi Networks Supporting Unlimited Number of Concurrent Connections. (8th July 2015) - Choi, Min; Park, Jong-Hyuk; Yi, Gangman
In the past, we used to call the name of members for the purpose of attendance checking by managers (or instructors). They verify the identity of member's participation by human recognition using facial and voice matching. This approach is time-consuming because the number of members is getting increased. Moreover, they may have to recheck any of the students' presence at the end of the period manually. In this research, we offer a convenient novel attendance checking method to take advantage of Wi-Fi 802.11x technology. Our application initiates AP mode Wi-Fi service for checking attendance of users in which a token is generated only to a person who is close to a manager. If a member has the token, the smart application of the member will connect and report to attendance server. Otherwise, the smart application of the member will report to the server that the users/students are not near the manager. By this way managers/instructors can easily check the member's attendance. In addition, this research proposes a novel concept that unlimited number of devices can be supported. We make use of Wi-Fi scan (rather than connect) to the manager's AP enabled smart devices, resulting in an enhanced scalability.